A Game-Based Approach to Manage Technostress at Work - Pasini, M; Arenas, A.; Brondino, M.; Di Marco, D.; Duarte, A.P.; Carvalho, C.V.; Silva, S.A. (Methodologies and Intelligent Systems for Technology Enhanced Learning, 11th International Conference. MIS4TEL 2021. Lecture Notes in Networks and Systems, 2021)
Work-related stress is a dangerous and expensive problem because it affects performance, and, if prolonged, can even result in serious health problems. With the advance towards the ubiquitous use of digital technology at work, a new form of work-related stress is emerging: techno-stress. Small and medium enterprises (SMEs) have few, if any, resources to deal with this issue and lower access to experts. This paper describes the design, development, and implementation of a game-based training program, named DESTRESS, which aims to provide an innovative Vocational Education and Training (VET)-based solution to help managing this problem. Building on existing research, a curriculum was developed, supported by an innovative Digital Training Platform using the latest techniques in game-based training and gamification, complemented by a set of practical tools and resources to facilitate the transfer of learning into the workplace.